MAKNA SIMBOLIK TARI BEDHAYA TUNGGAL JIWA DALAM RANGKAIAN UPACARA TRADISI GREBEG BESAR DI KABUPATEN DEMAK - , Sestri Indah Pebrianti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The residents in Demak regency, as a unit of society that live in northen coast of Java, has special events and they have important meaning. One of the important events for Demak society is when they welcome the Idul Adha day, Demak society always looks forward to the Grebeg Besar ceremony. To increase the interest of society, the Grebeg Besar ceremony is more developed and has additional in program. One of them is additional dance program named Bedhaya Tunggal Jiwa. The Bedhaya becomes the important element in Grebeg Besar ceremony. In this reseach, phenomenon that will be interesting to be studied (a). Why Bedhaya Tunggal Jiwa dance is showed?, (b). How the pattern of the show is?, (c). What the symbolic meaning of Bedhaya Tunggal Jiwa dance is?. In understanding the phenomenon happened in Bedhaya Tunggal Jiwa, this research applies the qualitative method to discover all the field data in explaining the problems occur. The result of field data, processed and written in descriptive analysis method etnokoreologi approach. That approach is done by textual and contextual analysis. The textual study, can lineout or describe in detail about the structure in Bedhaya Tunggal Jiwa dance, while the contextual study can reveal socio-cultural condition the residents in Demak regency. Bedhaya Tunggal Jiwa is one of the cultural elements in Demak society that is showed as a part of series traditional ceremony Grebeg Besar in Demak regencey. The presences human aesthetic need and also create the harmony of human and their environment. The performance of Bedhaya Tunggal Jiwa consists of several elements, including: motion, floor pettern, music, make up, clothing, properties and place of performing that overall is simple. The research result shows that Bedhaya Tunggal Jiwa is understood as teaching of life that cantains togetherness, unity and discipline to archive the useful purpose of live individually or in group. The symbolic meaning is contained in motion, floor pattern, costume, dance accompaniment, and properties that appropriate with the socio-cultural condition in Demak regency. The symbolic elements showed in the equipment that is used in the ceremonial series, the dancer actions, directions and number, integrity and social. The whole show vertical and horizontal relation activities of human being.